2003
DOI: 10.1051/agro:2002073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Toxicity on Plant Growth and Metabolism: I. Zinc

Abstract: Zinc toxicity and problems with regard to tolerance and ecological significance are briefly discussed. Differential tolerance of plant genotypes exposed to zinc toxicity is a more promising approach to enrich our understanding of zinc tolerance in plants. Knowledge concerning the physiology and biochemistry with regard to phytotoxicity, uptake and transport of zinc and tolerance and its characterization are also discussed. The cytotoxic effects of zinc on plants are elucidated. The major change was seen in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(106 citation statements)
references
References 120 publications
(143 reference statements)
6
91
0
9
Order By: Relevance
“…In addition, chlorophyll content of the duckweed was affected by copper. The declines in chla and chlb can be regarded as general responses associated with metal toxicity (Rout and Das 2003;Radic et al, 2010a). The loss of photosynthetic pigment content has been reported to cause a marked effect on the entire metabolism of duckweed (Radic et al, 2010a).…”
Section: Tablementioning
confidence: 99%
“…In addition, chlorophyll content of the duckweed was affected by copper. The declines in chla and chlb can be regarded as general responses associated with metal toxicity (Rout and Das 2003;Radic et al, 2010a). The loss of photosynthetic pigment content has been reported to cause a marked effect on the entire metabolism of duckweed (Radic et al, 2010a).…”
Section: Tablementioning
confidence: 99%
“…Chromium in particular, being highly soluble and bioavailable, exerts toxic effects on biological systems arising from the possibility of free-diffusion across the cell membrane and its strong oxidative potential (Shanker et al, 2005) whereas Zn-induced damage to living systems mainly includes impairment in functioning of several essential enzymes involved in metabolism (Rout and Das, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Amaral Sobrinho et al (2009) suggested that these soil variables have a strong influence on the adsorption and the consequent availability of heavy metals in soil. According to Maschner (1995), the root system is affected by Zn toxicity conditions, mainly in susceptible varieties; in addition Rout and Das (2003) reported that Zn toxicity was associated with changes in the root physiology, thereby inhibiting the elongation root.…”
Section: Resultsmentioning
confidence: 99%